Determinan Pertumbuhan Laba PT. Sinergi Gula Nusantara MKSO Kebun Sei Semayang Berdasarkan Kinerja Keuangan - Lisa Amanda; Seprida Hanum Harahap; Nadia Ika Purnama (Ali Institute of Research and Publication, 2026)
Problem in this study is how the determinants of profit growth of PT. Sinergi Gula Nusantara MKSO Kebun Sei Semayang based on the company's financial performance. This study aims to analyze the effect of capital structure, company size, and sales growth on profit growth at PT. Sinergi Gula Nusantara MKSO Kebun Sei Semayang. The research method used is quantitative research. The sampling technique uses saturated sampling, where the entire population is used as a research sample. The sample used is the company's monthly financial reports for the last five years with a total of 60 data samples. The data collection technique is carried out through documentation of the company's financial reports. The data analysis technique used in this study is multiple linear regression analysis using the SPSS program and classical assumption testing, t-test, and F-test. The results of the study indicate that partially the capital structure does not have a significant effect on profit growth, while company size and sales growth have a significant effect on profit growth. Simultaneously, capital structure, company size, and sales growth have a significant effect on profit growth at PT. Sinergi Gula Nusantara MKSO Kebun Sei Semayang. Keywords: Capital Structure, Company Size, Sales Growth, Profit Growth